A study on how international collaboration & management trainee programs contribute towards human capital development at Malaysia Airports Holdings Berhad / Nurena Abdullah (Faculty of Business and Management, 2006)
Recently, many organization concerns toward the development of human capital. They are aware that human capital is the most important asset for the organization in order to maintain a high culture business performance in the organization. Through that, this research is to study what are the important of human capital development at Malaysia Airports Holdings Berhad (MAHB). The research also examines the human capital development at MAHB especially into the program of International Collaboration and Management Trainee Program. Beside that, it also evaluates the impacts of each of the programs towards the staff performance and identifies the barriers and challenges along the implementation program. Through the purpose of the research, the researcher found that they are many programs are implemented at MAHB in order to their improve human performance. MAHB develop Career Development Program which has 9 winning approaches to enhance the staffs' performance. The 9 winning approaches are the reasons to fit the right people with the right competencies to the right job at the right time. However, in practicing the programs, there are many challenges and barriers incurred like lack of commitment from participants, poor program implementation, communication breakdown, language barriers and many more. To overcome the challenges and problems, this research also stated the best way on how to improve the programs for the future.